2009
DOI: 10.1111/j.1476-5381.2009.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular changes in spontaneously hypertensive rats are improved by chronic treatment with zofenopril

Abstract: Background and purpose:The aim of this study was to investigate the effect of chronic treatment with antihypertensive and non-antihypertensive doses of zofenopril on cardiovascular changes in spontaneously hypertensive rats (SHR). Experimental approach: Male SHR were treated with 0.5 or 10 mg·kg -1 per day of zofenopril (Z0.5 and Z10) for 3 months. SHR and Wistar-Kyoto rats (WKY) receiving vehicle were used as controls. Systolic blood pressure was measured using the tail cuff method. Left ventricular weight/bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
2
17
2
2
Order By: Relevance
“…The influence of perindopril on vascular remodeling may be blood pressure dependent, or it may mediated by non-ANG II mechanisms, as ACE is responsible for both production of ANG II and degradation of the vasoactive bradykinin (10). ACE inhibitors are effective, however, in controlling vascular remodeling, independent of blood pressure, and aortic stiffening as a result of fibrosis can be reversed by ACE inhibition independent of bradykinin preservation (8,17).…”
Section: Discussionmentioning
confidence: 95%
“…The influence of perindopril on vascular remodeling may be blood pressure dependent, or it may mediated by non-ANG II mechanisms, as ACE is responsible for both production of ANG II and degradation of the vasoactive bradykinin (10). ACE inhibitors are effective, however, in controlling vascular remodeling, independent of blood pressure, and aortic stiffening as a result of fibrosis can be reversed by ACE inhibition independent of bradykinin preservation (8,17).…”
Section: Discussionmentioning
confidence: 95%
“…A second limitation of this study is if a higher dose or time of treatment with LGF could have reversed to a higher extent the cardiovascular alterations in SHR. For example, it has been reported that high doses of zofenopril achieved a maximal effect after 4 wk of zofenopril treatment and were maintained over the following 4 wk, an effect that was not observed in the low-dose treatment (32). We are at initial stages of study of the cardiovascular actions of LGF, and these aspects, which have been largely analyzed in classical antihypertensive treatments, deserve further attention.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…, was able to markedly improve blood pressure, LVH, vascular remodeling, and endothelial dysfunction in SHR, but a lower dose (0.5 mg·kg Ϫ1 ·day Ϫ1 ) had a weaker effect (32). Furthermore, recently discovered actions of LGF treatment on arteries from apolipoprotein E knockout mice, involving a 25% reduction of atherosclerotic lesions (65), suggest that LGF has wider cardiovascular regenerative effects.…”
mentioning
confidence: 99%
“…40 minutes). Afterwards, ACh or SNP (from 10 -10 to 10 -4 M) was added cumulatively every 30 s in aliquots of 0.5 log units of concentration (34).…”
Section: Aortic Ring Preparationmentioning
confidence: 99%